고려시대 생산과 납세의 대상 - 이상국 (한국중세사연구, 2020)
This paper aims to explore what the subject to production and tax payment in Goryeo dynasty was under unstable conditions of agricultural productivity. To gain this purpose, the combining process of the peasant and the land was examined from a long-term perspective covering from Silla to the early Joseon and the process of tax payment in Stipend Land Law system was investigated as well. In consequence, I verify the land was allotted by the unit of ho[gongyeon, jeongho[ban-jokjeong]] from Silla to the early Joseon. And I also confirm ho[gongyeon, jeongho[ban-jokjeong]] organized by various households is the main agent of production. Moreover, the allotted land in the Stipend Land System was meant to collecting tax amount, and the Stipend Land System was managed to establish the farmers who was organized by the unit of a ho and to receive a land tax and tribute goods which was imposed on the allotted land.
Keywords: 생산단위; 납세단위; 휴한농법; 호; 공연; 정호[반족정]; unit of production; unit of tax payment; fallow land agricultural methods; ho; gongyeon; jeongho[banjokjeong]